Socio-Economic Determinants of Child Labour in the Hospitality Industry of Birendranagar, Surkhet - Pathak, Dhanush Chandra; Karki, Tej Bahadur; Paudel, Balkrishna; Pyakurel, Rahiesh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Child labour remains a critical global issue, defined as work that deprives children of their childhood, potential, and dignity, hindering their physical and mental development. Despite Nepal's ratification of numerous international conventions and the establishment of national laws to combat it, child labour persists, with an estimated 1.1 million children engaged in work. The hospitality industry is one sector where this exploitation is prevalent. This study focuses on the socio-economic, cultural, and institutional factors driving child labour in the hospitality industry of Birendranagar, the capital of Karnali Province, which has the highest child labour rate in Nepal.Objective: The general objective of this research is to explore and analyze the key socio-economic, cultural, and institutional factors contributing to the prevalence of child labour in the hospitality industry of Birendranagar, Surkhet.Methods: This study employed a quantitative research design. Data were collected in 2024 from 104 child labourers working in hospitality establishments in Birendranagar-07, Surkhet, using a convenience sampling method. Primary data were gathered through a semi-structured questionnaire, covering socio-demographic characteristics and the causes of child labour. Simple frequency distributions were used for data analysis, with results presented in descriptive and tabular forms.Findings: The study revealed that the majority of child labourers were male (89.42%) and aged between 12-16 years (69.23%). The primary drivers of child labour were economic: the pursuit of financial independence (36.54%) and poverty (36.53%) were the most cited reasons, with 44.23% of respondents working to increase their family's basic income. Cultural factors played a significant role, with 53.85% of respondents acknowledging its influence; 30.36% believed cultural acceptance normalizes child labour. Key social factors included a lack of community support for education (36.54%) and peer pressure to join the workforce (29.81%). A majority (62.50%) of respondents did not believe parental negligence was a cause.Conclusion: The prevalence of child labour in Birendranagar's hospitality sector is a multifaceted problem rooted in acute economic deprivation, compelling children to seek work for survival and financial autonomy. This economic driver is reinforced by cultural norms that normalize child work and social systems that fail to provide adequate educational and recreational alternatives. Addressing this issue requires a multi-pronged approach that goes beyond legislation to tackle the deep-seated economic and socio-cultural underpinnings.Implication: The findings provide critical evidence for federal and provincial governments to formulate targeted policies and interventions aimed at creating a child labour-free society. The study also offers practical insights for NGOs and INGOs working in child protection, emphasizing the need for initiatives that address poverty alleviation, shift cultural perceptions, strengthen community support for education, and enforce child rights.